1992
DOI: 10.21000/jasmr92010341
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Response to Organic Soil Amendments on Coarse Taconite Tailing

Abstract: Mine land reclamation rules in Minnesota require that tailing darns be constructed and vegetated to control wind and water erosion for dam stability, safety, and dust control. Coarse taconite tailing used in darn construction tends to resist vegetation stabilization due to several adverse edaphic factors that make it difficult to establish and maintain a diverse and productive vegetative cover that will meet State standards. The Bureau of Mines, in cooperation with the Minnesota Department of Natural Resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…The highest rate (89.6 Mg/ha) had significantly greater percent cover and biomass than any of the other treatments. Percent cover and biomass compare closely after 2 growing seasons with results from a study (Norland et al 1992(Norland et al , 1993) completed earlier using similar application rates of MSW compost. Subsequent findings (Norland et al 1994) showed that the 90% cover standard was achieved after 4 seasons.…”
Section: Ground Coversupporting
confidence: 70%
See 1 more Smart Citation
“…The highest rate (89.6 Mg/ha) had significantly greater percent cover and biomass than any of the other treatments. Percent cover and biomass compare closely after 2 growing seasons with results from a study (Norland et al 1992(Norland et al , 1993) completed earlier using similar application rates of MSW compost. Subsequent findings (Norland et al 1994) showed that the 90% cover standard was achieved after 4 seasons.…”
Section: Ground Coversupporting
confidence: 70%
“…In a companion study (Melchert et al 1994), MSW compost was applied to a tailing site to examine impacts on water quality and runoff. In recent years other studies have been initiated by the MDNR and the U.S. Bureau of Mines, studying the usefulness of MSW compost as a soil amendment for revegetating coarse !aconite tailing (Norland et al 1991(Norland et al , 1992(Norland et al , 1993. The objective of this paper is to assess tree growth and trace metal concentrations in leaf tissue for trees planted in coarse tailing plots treated with four rates of MSW compost.…”
Section: Introductionmentioning
confidence: 99%
“…During the third growing season (1992) there was a change in the cover variable response ( total, plant, litter, and bare tailing) to the main effect treatments compared to years one and two (Norland et al, 1991b(Norland et al, ,1992. Only the rate of MSW compost application and rate of fertilizer application resulted in statistically significant responses (Table 1), compost maturity had no statistically significant effect on the cover variables.…”
Section: Vegetation Litter and Bare Tailingmentioning
confidence: 97%
“…made using a cover-point optical point projection device (Norland et al, 1992). Cover measurements were taken in June and August 1992.…”
Section: Vegetation Sampling and Analysismentioning
confidence: 99%
“…Addition of organic residues to chat tailings had no effect on total nitrogen or phosphorus levels but increased levels of potassium (Norland, 1991). …”
Section: Journal Of Hazardous Substance Research 7-4 Discussion and Cmentioning
confidence: 95%